The Effects of Hydro-Alcoholic Extract of Fenugreek Seeds on the Lipid Profile and Oxidative Stress in Fructose-Fed Rats - Mohammad-Sadeghipour, Maryam (J Obes Metab Syndr, 2020)
BACKGROUND: Metabolic syndrome (MetS) is a complex clinical disorder that can lead to an increase in oxidative stress. Patients with this syndrome are at risk of diabetes and cardiovascular disease. The Trigonella foenum-graecum L. (fenugreek) plant has many therapeutic effects, including anti-diabetic and antioxidant. The present study aimed to investigate the effects of the hydro-alcoholic extract of fenugreek seeds (HEFS) on dyslipidemia and oxidative stress due to high-fructose diet-induced MetS. METHODS: In this experimental study, to induce MetS, animals received water containing 20% fructose for 8 weeks. After induction of MetS, 48 male Wistar rats (200?250 g) were randomized into six groups. HEFS was administered to animals at doses of 100 and 200 mg/kg orally for 4 weeks. Animal blood samples were collected to measure biochemical and antioxidant parameters of fasting plasma glucose (FPG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglycerides (TG), malondialdehyde (MDA), glutathione peroxidase (GPX), catalase (CAT), and total antioxidant capacity (TAC). RESULTS: The findings showed that the serum levels of FPG, TC, LDL-C, TG, and MDA were significantly reduced in HEFS-exposed groups compared with the control group (P<0.05). Also, significant increases in HDL-C, GPX, CAT, and TAC levels (P<0.05) were observed. CONCLUSION: Our results revealed that treatment with HEFS increases the levels of antioxidant enzymes, decreases FPG level, and at the same time, modifies the lipid profile in MetS. Therefore, HEFS may help to alleviate the risk of some chronic complications of this disease.